Eating and its disorders - Fox, John R. E.; Goss, Ken. (Chichester, West Sussex : Wiley-Blackwell, 2012)
'Eating and its Disorders features contributions by international experts in the field of eating disorders which represent an overview of the most current knowledge relating to the assessment, treatment, and future research directions of the study of eating-related disorders. Presents the newest models and theories for use in the treatment of patients with eating disorders. Written specifically to fulfill the needs of clinical psychologists and therapists. Includes coverage of important service related issues for working with people with eating disorders. Features chapters from a global group of authors which highlight differing methods and perspectives that can be incorporated into clinical practice'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Eating disorders -- Psychological aspects; Eating disorders -- Treatment; Needs assessment